PENGARUH JENIS KAKAO DAN KOMBINASI ZAT PENGATUR TUMBUH TERHADAP INDUKSI EMBRIO SOMATIK SECARA IN VITRO - Zuyasna Zuyasna; Erida Nurahmi; Rahmi Fajri (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
In an effort to increase the productivity of cocoa in Aceh, the government has carried out a cocoa plantation revitalization program for plants aged 25-30 years. The revitalization effort was constrained by the unavailability of quality seedlings. Alternatively, cocoa seedlings can be made available through vegetative propagations or through tissue culture techniques. Based on those facts, we have studied the inducing of callus and somatic embryos of cacao clones that were adaptive and highly productive in Aceh. The experiment was arranged in a completely randomized design, consisted of two factors. The first factor was the cacao genotype, having red and green fruits skin. The second factor consisted of six combinations of growth regulators 2,4-D and kinetin. The results showed that genotype of explants origin from cocoa red flowers responded very well in the formation of callus and somatic embryo formation. There was a significant interaction between genotype and growth regulator combinations on the explants in the number of somatic embryos formed. The best combination of concentrations growth regulator in response to somatic embryo in SCG (Secondary Callus Growth) medium was 3 mgL-1 2,4 D and 1 mgL-1 kinetin for explants from cocoa red flowers, and 1 mgL-1 2,4 D and 0 mgL-1 kinetin for explants origin from cacao green flowers.